New Insights in Oral Health and Diets - Varzakas, Theodoros; Antoniadou, Maria; Varzakas, Theodoros; Antoniadou, Maria (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The world of adult education needs information on instruments that provide behavioral changes and support the physical, emotional, and spiritual health of modern individuals. Under this scope, this Special Issue incorporates articles about modern perspectives on diet and coaching approaches that lead to new dietary habits.
English
Keywords: Research & information: general; Biology, life sciences; Food & society; diet; nutrition; oral health coaching; older adults; senior coaching; motivational interviewing; cognitive behavioral coaching techniques; independent elderly; healthy food; Mediterranean diet; food system; sustainability; conscious consumption; normal oral fibroblast; squamous carcinoma cell; Khat; myofibroblasts; cytotoxicity; cell death; food insecurity; mushroom nutrition; poverty; health promotion; health foods; probiotics; prebiotics; synbiotics; dental caries; effector strain; prevention; oral health; honey; Staphylococcus aureus; Streptococcus mutans; Fusobacterium nucleatum; antibacterial activity; oral cavity; artificial saliva; breast milk; microbiome; lactic acid bacteria; entero-mammary pathway; n/a